Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Dengan Metode Improve Disertai Embedded Test - Siti Khayroiyah; Hidayat Hidayat (Jurnal MathEducation Nusantara, 2018)
Abstract This study aims to determine the improvement of the ability of each aspect and the overall aspects of problem solving of students mathematics, with learning using IMPROVE method accompanied by embedded test to lead to the purpose of this study is to examine: (a) students' mathematical problem solving ability seen from each aspect and overall aspects before and after learning using IMPROVE method along with embedded test, and regular learning along with embedded test; (b) student activities and attitudes toward learning by IMPROVE method along with embedded test, (c) problems that arise during learning by applying IMPROVE method along with embedded test. This study is an experimental study in the form of pretest-postes control group design, with the subject of 81 students at AN-NIZAM Private High School in Medan. The instrument used to collect the data in this study consists of mathematical tests containing mathematical problems to measure students 'mathematical problem solving skills on the subject of Equation and Quadratic Inequality, student attitude questionnaire with Likert scale model to see students' attitudes toward learning by IMPROVE method accompanied by embedded test and observation sheet of student activity in learning Keywords: Problem Solving Abilities, Improve and Embedded Test Methods